Niveles de inclusión de Tithonia Diversifolia en pollos de carne como fuente de fibra y pigmento. - López Herrera, Elgie Rubén (2023)
This research was carried out in the experimental poultry house of the Animal Nutrition Center I+D+i of the National University of Loja, with the objective of evaluating the inclusion levels of Tithonia diversifolia in broilers as a source of fiber and pigment, For the development of the present investigation, a completely randomized block design was applied, with a population of 300 one-day-old Cobb 500 chickens of homogeneous weight. Three treatments were used: T1 (with 0 % inclusion), T2 and T3 (with 5 and 10 % inclusion of buttercup). The results obtained for productive parameters such as feed conversion and weight gain were higher when the inclusion level was 5%. The same behavior was observed for intestinal integrity with values for villus length 773 μm and epithelium height 52.5 μm; crypt depth 70.0 μm and muscle width 134.9 μm in T1. However, in chick pigmentation, it was appreciated that tarsus (66.54) and muscle (50.71) brightness was higher for the control treatment. The highest weight (2550.01 g) and carcass yield (83.0%) was obtained when 5% buttercup was applied. It is concluded that the application of buttercup (Tithonia diversifolia) can be used as a supplement in the diets of fattening birds, with a range not exceeding 10%, in order not to alter the production parameters, taking into account the nutritional contributions that it contains. It is recommended to apply the use of buttercup fodder in the feeding of meat birds because one of its benefits is to contribute to the productive performance.